Assessment of causality association between serum adiponectin levels and the risk of Alzheimer’s disease and Parkinson’s disease: a Mendelian randomization study - Lin, Jiali; Lei, Langhuan; Liang, Qiuyu; Huang, Xiaozhi; Ding, Yanping; Pan, Liuxian; Yang, Jianrong; Li, Wei (Frontiers in Neurology, 2025)
BackgroundUntil recently, the association between circulating adiponectin (ADPN) levels and the risk of Alzheimer’s disease (AD) and Parkinson’s disease (PD) remained unclear.MethodsWe utilized public data from the IEU GWAS database to conduct a two-sample bidirectional Mendelian randomization (MR) analysis and multiple sensitivity analyses. The MR analysis was performed using the aggregated data, with the genetic risk score (GRS) serving as an instrumental variable.ResultsThe MR analyses revealed no significant causal association between genetically determined ADPN levels and the risk of AD (ORIVW = 0.852, 95% confidence interval [CI]: 0.586–1.117, p = 0.235) or PD (ORIVW = 0.830, 95% CI: 0.780–1.156, p = 0.606). Conversely, neither AD nor PD demonstrated any causal association with ADPN levels. The GRS approach yielded similar results (p > 0.05). However, it exhibited a negative correlation with interleukin 1β (IL1β, βIVW = −0.31; 95% CI: −0.55 to −0.07, p = 0.011). The Cochrane’s Q test and MR-PRESSO analysis revealed no evidence of pleiotropy.ConclusionOur findings provide no evidence to substantiate a causal relationship between ADPN levels and the risk of AD and PD or vice versa. However, elevated levels of ADPN may correlate with lower levels of IL1β.